Environmental education and the 2030 Agenda: in the perception of managers of a teaching network (Research, Society and Development, 2021)
With the objective of analysing the perception of the managers of a teaching network regarding the practice of Environmental Education and the 2030 Agenda, from the perspective of Institutional Theory, this research was structured as a descriptive quantitative, occurred through the application of a questionnaire to school directors. A return of 21 was obtained, from a universe of 51 respondents, corresponding from August 2019 to March 2020. The data were tabulated using the Likert Scale and passed through the statistical/econometric manager STATA. It was concluded that the Sinodal Education Network is not yet in any phase of the four variables of the Institutional Theory, codification, incorporation, reproduction and institutionalization, regarding the demands of the National Environmental Education Policy (Law 9.795/1999) and 2030 Agenda. These results contribute to the managers of the Sinodal Network by the asymmetry of the information. For the future research, it is suggested to apply in other educational segments, public as well as private and, at all levels, using digital platforms for greater participation. Identifying whether Environmental Education is institutionalized or not, allows other educational control organ and society to benefit, both from the practical contribution and the motivation that it is possible to fomente new behaviors in favor of the environment.